ANALISIS FAKTOR-FAKTOR PENERIMAAN INTERNET BANKING DENGAN MENGGUNAKAN PENDEKATAN TECHNOLOGY ACCEPTANCE MODEL (TAM) DENGAN PENAMBAHAN PERAN MOTIVASI EXTRINSIC DAN INTRINSIC - Gusi Putu Lestara Permana (Universitas Pendidikan Nasional, 2017)
Technology Acceptance Model (TAM) is a model developed to predicting the factors that influence use of some technology by user. The purpose of this study was to test to test empirically the the effect of extrinsic and intrinsic motivation for acceptance internet banking. This study added perceived enjoyment variable as a proxy for intrinsic motivation. Data were analyzed using Stuctural Equation Model (SEM) with Partial Least Square (PLS). This study uses 70 respondents who use SINTESIS for their learning process. The results of the Partial Least Square (PLS) support the proposed research model, but the variable perceived perceived ease of use did not signicantly influence attitude towards using technology, the perceived enjoyment that added in this research has a significant effect on the attitude towards using technology and behavior intention to use, while others supported the hypothesis.Keywords: Technology Acceptance Model (TAM), extrinsic and intrinsic motivation, perceived enjoyment,